Degradation of two novel congenital TTP ADAMTS13 mutants by the cell proteasome prevents ADAMTS13 secretion. Issue 147 (November 2016) - Underwood, Mary; Peyvandi, Flora; Garagiola, Isabella; Machin, Samuel; Mackie, Ian
Abstract: Introduction: Over 150 mutations have been identified in the ADAMTS13 gene in patients with congenital thrombotic thrombocytopenic purpura (TTP). The majority of these (86%), lead to reduced (< 50%) secretion of mutant recombinant ADAMTS13. The mechanism by which this occurs has not been investigated in vitro . Two novel ADAMTS13 mutations (p.I143T and p.Y570C) identified in two congenital adolescence onset TTP patients were studied, to investigate their effects on ADAMTS13 secretion and subcellular localisation. Materials and Methods: HEK293T cells were transiently transfected with wild type or mutant ADAMTS13 cDNA. Immunofluorescence and confocal microscopy were used to study localisation within the endoplasmic reticulum (ER) and Golgi. The cell proteasome and lysosomes were inhibited in cells stably expressing ADAMTS13 to investigate degradation of ADAMTS13 by either organelle. Results: Both mutations severely impaired secretion and both mutants localised within the ER and Golgi. Proteasome inhibition led to the intracellular accumulation of both mutants, suggesting proteasome degradation. Lysosome inhibition on the other hand did not lead to increased intracellular accumulation of the mutants. Conclusions: Proteasome degradation of these ADAMTS13 mutants contributed to their reduced secretion. Highlights: Relations exist between the ADAMTS13 gene and congenital TTP phenotype. We studied the novel p.I143T and p.Y570C congenital ADAMTS13 mutants. Both severely impaired ADAMTS13 secretion and activity mirroring plasma levels. Both mutants were degraded within the cell by the cell proteasome.